Effects of carbohydrate gel ingestion with different timing on blood glucose response and subjective fatigue during prolonged exercise - Goto, K.; Uchida, H. (Advances in Exercise and Sports Physiology, 2013)
Purpose: The purpose of the present study was to compare the effects of carbohydrate gel at different times before exercise on the metabolic response and exercise performance during 80 min of high-intensity intermittent cycling. Methods: Seven male triathletes completed four different trials in a randomized, placebo-controlled, bouble-blinded design [placebo ingestion immediately before the exercise (P0) , carbohydrate ingestion immediately before exercise (C0), 45 min before the exercise (C45) or 120 min b fore the exercise (C120)]. Results and discussion: Immediately before exercise, the serum insulin concentration was significantly higher in the C45 than in the other trials. Blood glucose concentration was significantly lower in the C45 than in the P0 and the C0 during the initial part of the exercise. During the exercise, the C0 showed the highest glucose concentration. During the latter half of the exercise period, the C0 and C120 revealed a significantly lower average rating of perceived exertion (RPE) compared with the P0. There was no difference in RPE between P0 and C45. These findings i ndicate that carbohydrate gel ingestion immediately before exercise resulted in a maintained higher glucose concentration and lower subjective fatigue, especially during the latter half of the 80-min exercise period.